Outing representation: lesbian, gay, bisexual, trans and queer politicians' narratives. Issue 2 (1st June 2019) - Tremblay, Manon
Abstract : In recent years, more out-of-the-closet lesbian, gay, bisexual, trans and queer individuals have entered parliaments. Their visibility raises the question of how they imagine that their non-heteronormative sexuality interferes with their mandate of political representation. Based on interviews with 20 out of the 25 openly lesbian, gay and bisexual legislators in Canada in 2017, this article shows that they do imagine numerous ways in which being out of the closet empowers their role of representation. Without a doubt, being proudly visible is an asset for lesbian, gay and bisexual legislators.